Bilateral sternocleidomastoid tumor of infancy: a rare diagnostic dilemma - Goel, Sachin; Jain, Neha; Narang, Ekta; Roy, Suparna (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Sternocleidomastoid tumor of infancy (STOI) is a common cause of neck mass in the neonatal period. However, STOIs presenting bilaterally is a rare finding in medical literature. We herein report an unusual case of a bilateral STOI in a five-week infant. The child was given physical therapy which consisted of active and passive physical exercises, warm compresses and massage. Within 10 weeks the swellings reduced considerably in size. Bilateral, firm masses are often confused with lymphadenopathy and are inadvertently treated with antibiotics. Hence, STOI should be kept as an important differential diagnosis for neck mass in the neonatal period.